Old Testament abstracts - Catholic Biblical Association of America (Washington, DC : Catholic Biblical Association of America, 2005)
Includes indexing and abstracts for journal articles, monographs, multi-author works, and software related to Hebrew Bible (Old Testament) studies. All abstracts are in English, regardless of the language of the original work. The capability to search by specific scripture passages is useful.
Keywords: Bible. -- Criticism, interpretation, etc. -- Abstracts; Bible. -- Criticism, interpretation, etc. -- Periodicals -- Indexes